Significance of Clinical and Laboratory Variables in Early Detection and Prognosis of Malignant Lymphoma - Aiyesha Humaira , Syed Samiullah, (Journal of Rawalpindi Medical College, 2017)
Background: To study clinical, laboratory and radiological variables including bone marrow assessment in patients with malignant lymphomas. Methods: In this cross sectional study cases of malignant lymphoma were included. Clinical variables included age, gender, lymphadenopathy and hepatosplenomegaly. Laboratory variables included blood complete counts and bone marrow aspiration and bone trephine biopsy.Immunohistochemistry was performed to identify the specific lineage and developmental stages of lymphoma.Serum LDH, BUN, Creatinine, and SGPT were also performed . Statistical analysis were performed by Student t-test and Pearson Chi Square test Results: Hepatosplenomegaly, Haemoglobin, CT scan chest abdomen and immunohistochemistry were found significant factors in patients diagnosed to have lymphoma with bone marrow involvement. Variables such as WBC, BUN, Creatinine, LDH and SGPT had no significant correlation. Conclusion: The Variables in the study are in favour of the previous studies. Whereas regarding serum LDH levels the results were found insignificant which are not in favor of previous studies .